Basics of PET Imaging Physics, Chemistry, and Regulations - Saha, Gopal B.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
This revised edition of Basics of PET Imaging presents an unparalleled text on the basics of PET imaging technology. Distinguished author, Dr. Gopal B. Saha, has updated his previous bestselling work with concise chapters on PET fundamentals, including: Basic physics Instrumentation and data acquisition Production of PET radionuclides Performance characteristics of PET scanners Regulatory and reimbursement issues To maximize understanding, and to help technologists and residents prepare for board exams, chapters include pertinent basic science and equations along with sample problems and practice questions. The remarkable combination of Dr. Saha$1 (Bs brevity and clarity of content once again makes this edition an ideal reference book for nuclear medicine professionals interested in the basics of PET imaging.s
Radioactive Decay and Interaction of Radiation with Matter -- PET Scanning Systems -- Data Acquisition and Corrections -- Image Reconstruction -- Storage, Display, and PACS -- Performance Characteristics of PET Scanners -- Cyclotron and Production of PET Radionuclides -- Synthesis of PET Radiopharmaceuticals -- Regulations Governing PET Radiopharmaceuticals -- Reimbursement for PET Procedures -- Design and Cost of PET Center -- Procedures for PET Studies.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Medicine & Public Health; Nuclear Medicine; Imaging / Radiology